(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This study examines the functional-pragmatic nature of the epithet in literary discourse. Traditionally regarded as a stylistic ornament, the epithet is reinterpreted here as a pragmatic unit that shapes evaluation, emotional intensity, and reader perception. Drawing on functional stylistics and pragmatic theory, the article analyzes epithets as discourse-level mechanisms contributing to implicit meaning construction. The research employs qualitative discourse analysis of selected English literary texts. The findings demonstrate that epithets function as evaluative markers, emotional intensifiers, perspective-framing devices, and instruments of pragmatic influence. The study expands the theoretical understanding of epithets within discourse-oriented and pragmatic frameworks.